Spatial Distribution and Contamination Assessment of Lead (Pb) in the Seawater and Surface Sediments of the Coastal Area of Prigi Bay, Trenggalek, East Java - Defri Yona; David Vernandes; Rarasrum Dyah Kasitowati; Syarifah Hikmah Julinda Sari (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsConcentration of lead (Pb) in the surface water and sediment were analyzedThe ecological risks of metal in the ecosystem were assessedPb concentration in the surface water and sediment were observed in the similar range Pb in the study areas has low ecological risk indexConcern on Pb contamination in Prigi Harbor is neededAbstractThis study attempts to measure the spatial distribution of Pb in the seawater and surface sediments and to analyze its potential harmful effect in the surface sediments of the coastal areas of Prigi Bay, Trenggalek. Prigi Bay has been considered as one of the harbors with substantial activities from fisheries, tourism, and domestic events in Indonesia. These activities may discharge heavy metals, e.g., lead (Pb) into the environment and bring hazard to animal and human life. Data for Pb concentrations were collected from two stations near Prigi Harbor (Stations 1 and 2), one station in the Prigi Beach (Station 3) and two stations near the river mouths (Stations 4 and 5). Water quality parameters (temperature, salinity, pH, and DO) were also measured. Stations 1 and 4 displayed a higher concentration of Pb in the seawater than in the surface sediments. On the other hand, Stations 3 and 5 showed a higher concentration of Pb in the surface sediments than in the seawater. Pb concentration in the seawater was 0.22-0.60 mg/kg, and in the surface, sediments were in the range of 0.40-0.57 mg/kg. According to the analysis of contamination factor (CF), the study sites have a low degree of contamination from heavy metal Pb (CF < 1). The result was also supported by the potential toxicity of Pb to the benthic environment around Prigi Bay that was still considered low (E < 40). In spite of the low degree of contamination and low potential toxicity from Pb, concern regarding the heavy metal pollution in the study areas is still needed due to substantial activities that can contribute to the accumulation of heavy metal in a long time.